Effectiveness of Various AB Mix Concentrations on the Growth and Anatomy of Corn Plants (Zea mays L) in Hydroponic Systems - Hidayatullah, Careca Sepdihan Rahmat; Priambodo, Okta Nindita; Sutanto, Oentari Prilaningrum; Arrufitasari, Putri Nur; Handini, Aline Sisi (Jurnal Agroekoteknologi Tropika Lembab, 2025)
Corn (Zea mays L.) is the most widely cultivated cereal crop globally, serving as a vital source of food, animal feed, and biofuel. Efforts to improve corn production and ensure food security continue through advancements in fertilization and cultivation techniques. This study investigates the effect of different concentrations of AB Mix fertilizer on the growth and anatomical development of corn grown using an efficient floating hydroponic system. The experiment was conducted in a greenhouse at the Cikabayan Bawah Garden, Bogor Agricultural University, Bogor, Indonesia, located at an altitude of 234 meters above sea level. A completely randomized design (CRD) was used, with one factor—AB Mix concentration—at three levels: ½×, 1×, and 2× the standard concentration. Each treatment was replicated six times, resulting in 18 experimental units. Results showed that the 2× AB Mix concentration significantly enhanced plant performance, with a 107% increase in growth compared to the ½× concentration at 4 weeks after sowing (WAS). Parameters such as plant height, shoot fresh weight at 4 WAS, root fresh weight at 3–4 WAS, and total fresh weight at 4 WAS all showed marked improvements with the 2× treatment. These findings indicate that doubling the standard AB Mix concentration is optimal for hydroponic corn cultivation up to 4 WAS. Further studies are recommended to assess the physiological responses and yield outcomes across different corn varieties under varying AB Mix concentrations